Pengaruh Kepemimpinan Situasional Dan Etos Kerja Terhadap Kinerja Pegawai Melalui Iklim Organisasi Sebagai Variabel Intervening Pada Politeknik Pembangunan Pertanian Gowa - Delia Esiana Tangdigling; Idayanti Nursyamsi; Ria Mardinana Yusuf (Hasanuddin Journal of Business Strategy, 2019)
This study aims to determine the effect of Situational Leadership and Work Ethics on Employee Performance through Organizational Climate as an Intervening Variable in Gowa Agricultural Development Polytechnic. The type of data used in this study is divided into two, namely qualitative and quantitative data. The population in this study were all State Civil Apparatus at the Gowa Agricultural Development Polytechnic, which until 2018 totaled 98 people. A sample of 98 employees based on the population. The sampling technique used is the nonprobability sampling method. Data collection techniques used were observation, interviews, questionnaires, and documentation. Data were analyzed using path analysis. The results of this study indicate that situational leadership has a positive and significant effect on organizational climate. The better the leader applies situational leadership, the better the climate for the organization will be and conducive. Good situational leadership will create a good organizational climate so that it will have an impact on increasing employee performance. Work ethic has a positive and significant effect on organizational climate. The better the work ethic that is owned by employees, it will support the creation of a good organizational climate. The better the work ethic that is owned by an employee it will lead to a good organizational climate, which has an impact on increasing employee performance.